Pengenalan Literasi Keagamaan Melalui Metode Kreatif Dan Interaktif Untuk Anak Usia Dini - Imroatun Imroatun; Abda Billah Faza Muhammadkan Bastian; Siti Imoy; Fadila Dea Pandini; Fattah Setiawan Santoso (Ulumuddin)
This research aims to increase the understanding, knowledge and skills of teachers and parents in applying creative and interactive methods in introducing religious literacy for early childhood, with an active participation approach. With these activities, parents and teachers can reflect on further learning both at school and at home. This research was carried out at RA Al Wardah, Pandeglang Regency, involving RA teachers in Pandeglang and parents. Religious literacy in early childhood plays a crucial role in forming a child's character and identity. This developmental phase is considered very important, considering that the main foundations in children's lives are built in this period. In this context, the availability of information and technology in the modern era is challenging, and children are vulnerable to distraction from religious values ​​in everyday life. Therefore, the right approach in building the basis of religious literacy in early childhood is a must. Children will be more involved and enthusiastic in understanding religious teachings and applying these values ​​in everyday life. The creative approach involves the use of stories, games, and art activities, while the interactive method involves discussion, the child's active role, and participation in group activities. Strengthening religious literacy in early childhood through creative and interactive methods aims to help them build a strong foundation in understanding and respect for religious values. It is hoped that this effort can form a young generation who is responsible, ethical and sensitive to religious values ​​in everyday life. It is hoped that this contribution can have a positive impact in forming the character of early childhood and developing a society that respects religious values.